MdSnRK1.1 interacts with MdJAZ18 to regulate sucrose-induced anthocyanin and proanthocyanidin accumulation in apple - Liu, Xiao-Juan (J Exp Bot, 2017)
Sugars induce anthocyanin biosynthesis in plants. As a conserved energy sensor, SnRK1 (SNF1-related kinase 1) is involved in sucrose-induced anthocyanin accumulation. However, the exact molecular mechanism by which SnRK1 regulates the biosynthesis of anthocyanins and proanthocyanidins (PAs) in response to sucrose in plants is not clear. In this study, it was found that MdSnRK1.1 interacted with MdJAZ18 protein which acts as a repressor in the jasmonate (JA) signaling pathway. MdSnRK1.1 then phosphorylated MdJAZ18 to facilitate its 26S proteasome-mediated degradation, which released MdbHLH3 thereby activating the expression of the regulatory and structural genes, thus finally promoting the biosynthesis of anthocyanins and PAs. Taken together, these results demonstrate the involvement of MdSnRK1.1 in sucrose-induced accumulation of anthocyanins and PAs. For the first time, our findings shed light on the molecular mechanism by which the crosstalk of sucrose and JA signaling regulates flavonoid biosynthesis.